Doing the right thing to get diamonds? Professional challenges and moral dilemmas - Marsden, Emma (Dutch Journal of Applied Linguistics, 2024)
In this response to Diamond is a scientist’s best friend, Emma Marsden reflects on her past roles as author and editor. She discusses the challenges for flipping journals to diamond models and for publishing in diamond journals and offers ways forward.